Analisis Yuridis Penyelesaian Sengketa Tanah Waris yang Belum Bersertifikat di Pengadilan Agama/Negeri - Abidin, Jenal; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Disputes over uncertified inherited land trigger serious issues regarding proof of rights, overlapping legal aspects, and the absolute competence of the Religious Court (PA) and the District Court (PN). This normative legal study, utilizing statutory, conceptual, and case approaches, examines the legal basis, judicial competence, evidentiary strength, and litigation obstacles of such cases. The results indicate that inheritance disputes among Muslims fall under the absolute competence of the PA. However, if they involve third parties, non-Muslims, or tort (perbuatan melawan hukum) claims, the PN may have jurisdiction depending on the legal construction. Evidentiary proof for uncertified land relies on girik, letter C, inheritance certificates, witnesses, and physical possession, although its strength remains inferior to registered land. Ultimate legal certainty must be pursued through land administration formatting via inheritance rights registration and certification.